Engaging Early Consumers: How BYD Leads EV Diffusion in Indonesia - Bagus Muhamad Adam; Agustinus Rusdianto Berto; Ignatius Haryanto (Institut Komunikasi dan Bisnis LSPR, 2024)
The electric vehicle (EV) market in Indonesia is experiencing rapid growth, with early adopters playing a pivotal role in its expansion. This study analyzes the digital marketing strategies of BYD and Wuling, two prominent EV brands, focusing on their Instagram content to understand how they target early consumer segments. Using the Diffusion of Innovation Theory as a framework, the study categorizes Instagram content into six main categories, with a deeper analysis of Product Information subcategories. Findings reveal that BYD emphasizes technological innovation, futuristic design, and comfort, aligning well with early adopters' preferences. In contrast, Wuling focuses on comfort and consumer interaction, appealing to a broader audience. The chi-square analysis confirms significant differences in content distribution between the two brands. These results highlight BYD’s strategic alignment with early consumer needs as a key factor in its market leadership. Future research should explore other platforms and consumer responses to optimize EV marketing strategies. This study is limited to Instagram content, and future research should include other social media platforms and consumer interviews for a broader perspective. The study contributes theoretically by advancing the application of diffusion of innovations theory in digital communication and offers practical insights for companies.